From the leaf to the community: Distinct dimensions of phytochemical diversity shape insect–plant interactions within and among individual plants. (17th April 2021) - Cosmo, Leandro G.; Yamaguchi, Lydia F.; Felix, Gabriel M. F.; Kato, Massuo J.; Cogni, Rodrigo; Pareja, Martín
Abstract: Plant secondary chemistry is known to be an important driver of plant–insect community structure across ecological scales. Recently, the concept of phytochemical diversity (PD) has been introduced to help describe variation in plant secondary chemistry and explain how this variation affects community structure. Previous studies show that PD among individuals and species results in phytochemical mosaics, known as the phytochemical landscape. However, plant traits can vary at finer scales, such as within individuals, and even a single host plant may be perceived as an entire phytochemical landscape by an interacting insect. Using the neotropical shrub Piper amalago, we tested and compared how herbivory, caterpillar biodiversity and plant–herbivore network structure are affected by the compositional (number and concentration of compounds) and structural (diversity of distinct chemical structures) dimensions of PD. We analysed variation among individual plants and among‐plant height strata within individual plants. This allowed us to decompose PD within and among plant individuals and analyse how variation at both scales affects the plant–herbivore network. We found that both within and among plants greater structural diversity decreased herbivore feeding damage. Furthermore, each dimension of PD has different effects on herbivore biodiversity and network structure depending on the scale of biological organization. Within plants, the compositional dimension, specifically low concentrations of compounds tentatively identified as Piper amides, increased herbivore biodiversity. This dimension also increased the capacity of strata within plants to mediate ecological cascades through direct and indirect effects on herbivore abundance in the plant–herbivore network. In contrast, a greater structural diversity among plants decreased herbivore biodiversity and the capacity of plants to affect all other herbivores and plants directly and indirectly in the network. Synthesis . Based on our results we expand the concept of the phytochemical landscape to multiple scales of biological organization and provide evidence that PD may be maintained by how its multiple dimensions have distinct roles across scales of biological organization. Abstract : Phytochemical diversity (PD) has multiple dimensions. In Piper amalago, greater diversity of chemical structures decreased herbivory, while compound identity affected herbivore biodiversity. Both dimensions affected how individual plants connect the interaction network. We expand the concept of the phytochemical landscape and show that PD may be maintained by how its multiple dimensions have distinct roles across scales of biological organization. Resumo: A química secundária de plantas é um estruturador importante das comunidades inseto‐planta em diferentes escalas espaciais. Recentemente, o conceito de diversidade fitoquímica foi introduzido para ajudar a descrever a variação na química secundária de plantas e explicar como essa variação afeta a estrutura de comunidades. Estudos anteriores mostraram que a diversidade fitoquímica entre indivíduos e espécies cria mosaicos fitoquímicos, conhecidos como a paisagem fitoquímica. No entanto, atributos de plantas podem variar em escalas muito pequenas, como dentro do mesmo indivíduo, e uma única planta pode ser percebida por um inseto como uma paisagem fitoquímica inteira. Usamos o arbusto neotropical Piper amalago para testar e comparar como a herbivoria, biodiversidade de lagartas e estrutura da rede planta‐herbívoros são afetados pelas dimensões composicional (número e concentração de compostos) e estrutural (diversidade de estruturas químicas) da diversidade fitoquímica. Analisamos variação entre indivíduos de planta assim como entre estratos de altura dentro de cada planta. Isso nos permitiu decompor a diversidade fitoquímica dentro e entre indivíduos de planta e analisar como essa variação afeta a rede planta‐herbívoro. Constatamos que, mesmo dentro de plantas individuais, maior diversidade estrutural diminui o dano causado por herbívoros. Também constatamos que cada dimensão da diversidade fitoquímica tem efeitos diferentes na diversidade de herbívoros e estrutura da rede de interações dependendo da escala de organização biológica. Dentro de plantas, a dimensão composicional, em particular baixas quantidades de compostos identificados tentativamente como amidas de Piper, aumentaram a diversidade de herbívoros. Essa dimensão também aumentou a capacidade de um estrato de mediar cascatas ecológicas a través de efeitos diretos e indiretos na abundância de herbívoros na rede planta‐herbívoro. Por outro lado, uma maior diversidade estrutural entre plantas diminui a diversidade de herbívoros e a capacidade de plantas de afetar outros herbívoros e plantas na rede direta‐ e indiretamente. Síntese . Com esses resultados expandimos o conceito de paisagem fitoquímica para múltiplas escalas de organização biológica e fornecemos evidência de que a diversidade fitoquímica pode ser mantida pelo papeis diferentes que ela tem em diferentes escalas espaciais.